Structural Characterization of T-Cell Kinases lck1 and Zap-70 in Rainbow Trout (Oncorhynchus Mykiss) Through Homology Modeling - Maisey-Munoz, K (Elsevier Ltd, 2025)
Early T-cell receptor (TCR) signaling is well defined in mammals but remains underexplored in teleosts such as rainbow trout. The proximal tyrosine kinases Lck and ZAP-70 initiate signaling by phosphorylating and decoding CD3 ITAM motifs. In rainbow trout, two sequences have been annotated for each kinase; their functional relevance is unclear. We combined multiple sequence alignments, homology modeling (SWISS-MODEL), and structure quality checks (VERIFY3D, Ramachandran) with peptide–protein docking of CD3ζ ITAMs and structural superposition against active ZAP-70 (PDB 4XZ1 ) to infer residue-level mechanisms for trout Lck1 and ZAP-70. In Lck1, the residues corresponding to human Y394 and Y505 (trout Y388 and Y499) are predicted to stabilize active and inactive conformations, respectively, supporting a conserved regulatory switch. For ZAP-70, Arg38 and Arg191 are predicted to form the canonical phosphotyrosine-binding pockets required for CD3ζ ITAM engagement. A trout-specific Phe310 at the interdomain interface may favor the autoinhibited state, thereby attenuating kinase activation, suggesting evolutionary fine-tuning. Docking indicated that Lck1 engages the CD3ζ ITAM in a human-like manner, whereas productive ZAP-70 binding required the activation-associated rearrangement seen in 4XZ1, consistent with mammalian mechanisms. These in silico analyses provide a structural framework for proximal TCR signaling in teleosts. Trout Lck1 harbors the elements needed to initiate ITAM phosphorylation, and ZAP-70 retains key features of ITAM recognition, with Phe310 potentially modulating activation. Experimental validation will be important to test these predictions. © 2025 Elsevier Ltd.